MORPHOLOGICAL AND HISTOLOGICAL ANALYSIS OF MALE DONKEY REPRODUCTIVE DUCTS: FROM DEFERENT DUCTS TO EJACULATORY PATHWAYS - Abou-Elhamd, Alaa Sayed (Science Journal of University of Zakho, 2025)
The anatomical and histological characteristics of the terminal deferent ducts, excretory ducts of the seminal vesicles, and ejaculatory ducts were examined in detail. The terminal deferent duct, located ventromedially to the excretory duct of the seminal vesicle, exhibited a small, irregular lumen with cyst-like invaginations into the vascular, fibromuscular connective tissue. Its lumen was lined by bi-layered columnar epithelium, with principal cuboidal cells and occasional basal flat cells. The connective tissue of the cranial deferent duct contained collagen, elastic fibers, and smooth muscle, transitioning towards diminished smooth muscle at the duct's terminal region. The ducts from either side merged to form common ejaculatory ducts, which entered the urethra at the Colliculus seminalis. At this junction, the epithelium changed to either stratified columnar or cuboidal types. The ejaculatory ducts exhibited lumens characterized by branched folds, which were lined with stratified columnar epithelium and reinforced by a dense network of collagenous and elastic connective tissue. Scanning electron microscopy revealed that the luminal surface of the ejaculatory duct was folded, irregularly oval, had nearly hexagonal epithelial cells with distinct borders, and abundant microvilli on the luminal surfaces. These findings provide a comprehensive understanding of the structural organization of these ducts and their role in the male reproductive system
Keywords: Seminal vesicle ducts; Deferent ducts; Ejaculatory ducts; Mullerian ducts